2022
DOI: 10.1002/cbdv.202200494
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of Potential Insect Peptides against Biofilm‐Producing Staphylococcus aureus

Abstract: Biofilm-producing Staphylococcus aureus (SA) strains are frequently found in medical environments, from surgical/ wound sites, medical devices. These biofilms reduce the efficacy of applied antibiotics during the treatment of several infections, such as cystic fibrosis, endocarditis, or urinary tract infections. Thus, the development of potential therapeutic agents to destroy the extra protective biofilm layers or to inhibit the biofilm-producing enzymes is urgently needed. Advanced and cost-effective bioinfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In our study, we constructed a model of Staphylococcus aureus induced Osteomyelitis by knocking out the SDRC protein sequence of Staphylococcus aureus and infecting rat, founding that compared with wild type Staphylococcus aureus infected Osteomyelitismouse , its IL-6, TNFα The inflammatory indexes such as ALP, OST and RunX2 were significantly reduced, the infection of bone tissue was significantly lighter, and the osteogenic indexes such as ALP, OST and RunX2 were also significantly increased, suggesting that SDRC protein played a huge role in the occurrence and progress of Osteomyelitis infected by Staphylococcus aureus. Previous studies [19,31] have shown that the most important biological function of SDRC protein is its ability to promote the formation of bacterial biofilms, which is particularly important in the process of bacterial infection of the host [32,33] . Therefore, understanding the molecular mechanism mediated by SDRC protein is of great significance for the treatment of Staphylococcus aureus infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we constructed a model of Staphylococcus aureus induced Osteomyelitis by knocking out the SDRC protein sequence of Staphylococcus aureus and infecting rat, founding that compared with wild type Staphylococcus aureus infected Osteomyelitismouse , its IL-6, TNFα The inflammatory indexes such as ALP, OST and RunX2 were significantly reduced, the infection of bone tissue was significantly lighter, and the osteogenic indexes such as ALP, OST and RunX2 were also significantly increased, suggesting that SDRC protein played a huge role in the occurrence and progress of Osteomyelitis infected by Staphylococcus aureus. Previous studies [19,31] have shown that the most important biological function of SDRC protein is its ability to promote the formation of bacterial biofilms, which is particularly important in the process of bacterial infection of the host [32,33] . Therefore, understanding the molecular mechanism mediated by SDRC protein is of great significance for the treatment of Staphylococcus aureus infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ltd., Mumbai, India, through local vendors. The entire computational work was analysed on a Linux-Ubuntu 16.04 LTS workstation with several cheminformatics software packages (Swain et al, 2022a;Sahoo et al, 2022b).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the docking score (kcal/mol. ), the potent phytoconstituents were again docked manually in AutoDock to confirm the ligand's crystallographic binding mode and appropriate docking score through 3-D and twodimensional (2-D) molecular interactions with targets using the software BIOVIA-DSV-2019 (Swain et al, 2022a;Sahoo et al, 2022b).…”
Section: Target Protein and Ligand Structure Preparation For Molecula...mentioning
confidence: 99%
See 2 more Smart Citations